Update on diagnosis, pathophysiology, and management of diabetic kidney disease. Issue 6 (17th February 2021) - Sugahara, Mai; Pak, Wai Lun Will; Tanaka, Tetsuhiro; Tang, Sydney C. W.; Nangaku, Masaomi
Abstract: Diabetic kidney disease (DKD) is a chronic complication of diabetes mellitus which may eventually lead to end‐stage kidney disease (ESKD). Despite improvements in glycaemic control and blood pressure management with renin‐angiotensin‐aldosterone system (RAAS) blockade, the current therapy cannot completely halt DKD progression to ESKD in some patients. DKD is a heterogeneous disease entity in terms of its clinical manifestations, histopathology and the rate of progression, which makes it difficult to develop effective therapeutics. It was formerly considered that albuminuria preceded kidney function decline in DKD, but recent epidemiological studies revealed that a distinct group of patients presented kidney dysfunction without developing albuminuria. Other comorbidities, such as hypertension, obesity and gout, also affect the clinical course of DKD. The pathophysiology of DKD is complex and multifactorial, involving both metabolic and haemodynamic factors. These induce activation of intracellular signalling pathways, oxidative stress, hypoxia, dysregulated autophagy and epigenetic changes, which result in kidney inflammation and fibrosis. Recently, two groups of antidiabetic drugs, sodium‐glucose cotransporter 2 (SGLT2) inhibitors and glucagon‐like peptide‐1 (GLP‐1) receptor agonists, were demonstrated to provide renoprotection on top of their glucose‐lowering effects. Several other therapeutic agents are also being developed and evaluated in clinical trials. SUMMARY AT A GLANCE: This article reviewed recent advances in the pathogenesis and treatment of diabetic kidney disease (DKD). Special focus is put on the phenotypic heterogeneity of DKD, and the recent studies that showed the therapeutic benefits of SGLT2 inhibitors and GLP‐1 receptor agonists. Potential future therapeutic strategies are also explored.